The Relationship Between Self-Congruity with Sponsorship, Customer Involvement and Customer Loyalty - Elina, Abd Manan (2009)
The study examined the relationship between self-congruity with sponsorship, customer involvement and customer loyalty. Two research objectives were determined for this study. 168 respondents from Kelab Keusahawanan Universiti Utara Malaysia were involved in the study. A causal research method was employed, and self-administered questionnaire with five point Likert scale was used to collect data. Data were analyzed through correlation and multiple regressions analysis. The study found that there is positive relationship between self-congruity with sponsorship, customer involvement and customer loyalty. Customers with high degree of congruence with the sponsored event are more likely to involve with the event. As the level of self-image congruity increase, customers are more likely to prefer that sponsoring firm’s product. Highly involved customers with a sponsored event portray a high level of loyalty towards the sponsoring firms. Regression analysis revealed that customer involvement influenced customer loyalty greater than self-congruity with sponsorship, by explaining 44.5 percent of customer loyalty variance. The study ends with managerial and academic implications related to the study. Finally, several recommendations were proposed for future action.